Single-Cell Transcriptomic Analyses of the Developing Meninges Reveal Meningeal Fibroblast Diversity and Function - DeSisto, John; O’Rourke, Rebecca; Jones, Hannah E.; Pawlikowski, Bradley; Malek, Alexandra D.; Bonney, Stephanie; Guimiot, Fabien; Jones, Kenneth L.; Siegenthaler, Julie A. (Developmental cell, 2020)
The meninges are a multilayered structure composed of fibroblasts, blood and lymphatic vessels, and immune cells. Meningeal fibroblasts secrete a variety of factors that control CNS development, yet strikingly little is known about their heterogeneity or development. Using single-cell sequencing, we report distinct transcriptional signatures for fibroblasts in the embryonic dura, arachnoid, and pia. We define new markers for meningeal layers and show conservation in human meninges. We find that embryonic meningeal fibroblasts are transcriptionally distinct between brain regions and identify a regionally localized pial subpopulation marked by the expression of μ-crystallin. Developmental analysis reveals a progressive, ventral-to-dorsal maturation of telencephalic meninges. Our studies have generated an unparalleled view of meningeal fibroblasts, providing molecular profiles of embryonic meningeal fibroblasts by layer and yielding insights into the mechanisms of meninges development and function.